2022
DOI: 10.1007/s12247-022-09619-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving Antibacterial Efficiency of Curcumin in Magnetic Polymeric Nanocomposites

Abstract: In recent years, resistance to chemical antibiotics, as well as their side effects, has caused a necessity to utilize natural substances and herbal components with antibacterial effects. Curcumin, the major substance of Curcuma longa’s rhizome, was used as an antibacterial agent since ancient times. This work aimed to formulate a novel nanocomposite for the delivery of curcumin to overcome orthodox drugs resistance against bacteria and improve its efficacy. To fabricate targeting nanocomposites, first, Fe3O4 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…The FT-IR spectra of the components of nanoparticles, Plain-NP, free CUR, as well as the curcuminoid loaded NP were evaluated between 4000 and 1000 cm −1 and the results are shown in Figure 1 . The major signals of CUR in the spectra were similar to those reported in earlier studies [ 8 , 23 ].…”
Section: Resultssupporting
confidence: 87%
“…The FT-IR spectra of the components of nanoparticles, Plain-NP, free CUR, as well as the curcuminoid loaded NP were evaluated between 4000 and 1000 cm −1 and the results are shown in Figure 1 . The major signals of CUR in the spectra were similar to those reported in earlier studies [ 8 , 23 ].…”
Section: Resultssupporting
confidence: 87%
“…In the biomedical area, curcumin has been widely used as an antioxidant, anti-inflammatory, anticancer, antiapoptotic, and neuroprotective agent [ 61 , 62 , 63 ]. In the present study, curcumin was investigated for its antimicrobial properties against Gram-positive, Gram-negative, and fungal strains [ 64 , 65 ]. While previously published papers have demonstrated a considerably greater sensitivity for Gram-positive than Gram-negative bacteria [ 66 ], our results indicated similar antimicrobial efficiency towards all the tested strains, thus proving the potential of the current drug-delivery systems to be used for a wide spectrum of microbial species.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control group, the Cur-Free group had almost no killing effect on bacteria, while the number of bacterial colonies in the ZIF-8, Cur-ZIF8, and Cur-ZIF8-HA groups was significantly reduced. Curcumin is well known for its antibacterial effect; then why the result is contradicting previous reports? It is indeed antibacterial, and the MIC is 62.5 μg/mL. To ensure that the concentration used by Cur is promoting the proliferation and migration of fibroblasts, a low (7.5 μg/mL) was selected.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro tests showed that the hemolysis rates of ZIF-8, Cur-ZIF8, and Cur-ZIF8-HA were all lower than the acceptable value (5%) at concentrations of 5 and 10 μg/mL, which proved that they had good blood compatibility without any hemolysis. In addition to the hemolysis test and the toxicity assessment of normal cells, organic safety in mice has further studied whether the nanosystems have significant biological toxicity . After the treatment, H&E staining showed that compared with the control group, there were no histopathological changes in the main organs of mice (liver, heart, spleen, lung, and kidney) (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation